Introduction. Music: Intangible Heritage? - Elsa Broclain; Benoît Haug; Pénélope Patrix (Transposition)
Music holds a key place in the Intangible Cultural Heritage (ICH) of humanity as inventoried by UNESCO since its 2003 Convention for the Safeguarding of the ICH. More broadly, beyond the United Nations, “intangible heritage” seems to have become the dominant paradigm in processes of heritagisation and recognition of musical practices at the international level. Given the vast scope of this phenomenon, the aim here is to initiate a transnational, comparative approach to the relations between music and “intangible heritage”. Looking at the ways in which this notion (and/or the heritage apparatus that comes with it) is implemented, reformulated or contested in the field, and at its interactions with other categories and modes of action in use, this issue of Transposition invites us to ask: what does ICH do to music and, conversely, what does music do to ICH?Most of the studies assembled here deal with practices inscribed on the UNESCO lists, which are the subject of safeguarding programmes already in effect for some years. These “post-heritage” situations are examined in their diversity. Other articles plunge us into the process of preparing an ICH application, piercing straight to the difficulties and potential consequences of heritagising a musical practice. Some practices covered here are not candidates for the UNESCO lists but are engaged in local heritagisation systems that use the designations and some of the tools and modalities of action of ICH. Finally, several articles give voice to heritagisation actions with a separate approach or used as a form of protest.The singularity of music within ICH can be summed up in three recurring points: the “intangibility” of music caught up in these heritagisation processes; the specific intersections between music, power dynamics and territory in this context, particularly in regard to subaltern practices; and the performative nature of the heritage constructions at play, conceived as operative fictions.